Qualidade fisiológica e armazenamento de sementes de plantas matrizes de Dimorphandra gardneriana Tulasne - Ursulino, Marina Matias (2017)
The species Dimorphandra gardneriana Tulasne is a native Brazilian tree, propagated by seeds, whose fruits have high content of bioflavonoids rutin and quercetin, used in large scale by the pharmaceutical industry. Thus, it is necessary to evaluate the quality of the seeds produced in order to select seed plants for the seed harvest. The objective of this work was to evaluate the physiological quality of seeds of different D. gardneriana matrix plants, as well as their storage potential. In order to characterize the fruits and seeds of D. gardneriana, the biometrics were determined, while germination and vigor tests were performed (germination speed, seedling length and dry mass, conductivity electrical, accelerated aging, emergency in the field and tests of cold and x-rays). In order to store the seeds, different packages (aluminum foil, Kraft paper, cloth, plastic and bottles of polyethylene terephthalate - PET) were tested and in environments (laboratory natural, refrigerator and cold and dry chamber) for a period of 28 months, with evaluation of the water content, germination and vigor at the beginning and every 40 days of storage. The biometric characteristics of fruits and seeds of D. gardneriana are variable between the matrix plants, being indicated to 20 as one that owns seeds of larger size. By the results of the accelerated aging test the seeds of the matrix plant 11 are the most vigorous. Greenhouse and field emergence tests were efficient in separating the seeds of different D. gardneriana seedlings at vigor levels, and the seeds of the plants 19 and 20 were considered of better physiological quality. Cold and germination at low temperature highlight the seeds of the maturing plants 18, 19 and 20 as the most vigorous, whereas by the results of the tetrazolium test the most vigorous seeds were from the plants 2, 3, 6, 8 and 13. X - ray image was effective to evaluate the morphology of the seeds of different D. gardneriana matrix plants and its relationship with vigor. In storage, the seeds of D. gardneriana remained viable and with high physiological quality for up to 20 periods, with plastic and PET bottles being the most suitable for the storage of these seeds.